Atividade antioxidante e caracterização do perfil metabolômico da casca, semente e polpa das variedades Margarida, Breda e Geada do abacate (Persea americana) - Oliveira, Christean Santos de (2019)
Avocado (Persea americana) belonging to the Lauraceae family is considered a very important fruit of great commercial importance in the world, due to its high nutritional content and beneficial health effects, being mainly related to the source of nutrients soluble in lipids or phytochemicals, possessing a very expressive world-wide consumer market and that calls attention for its economic relevance quite expressive in most of the Brazilian states. Possessing more than 50 known species, avocado has as main Brazilian varieties Quintal, Fortuna, Geada, Margarida and Breda. Several studies have demonstrated the inverse association between the consumption of plant foods and the prevalence of chronic noncommunicable diseases, such as cancer, diabetes, cardiovascular diseases and degenerative diseases. In this way, the present work proposes to outline the metabolic profile of avocado, exposing the presence of bioactive compounds in their pulp, seed and bark through classical determinations of antioxidant activity and total phenolic content where it was found that the highest phenolic values are found in the seeds, being the largest of them (83,38mg GAE/g) ) in the Margarida variety and total flavonoids with lower values being 6.90mg QE/g the highest value found that is present in the bark of the Geada variety. With the physico-chemical characterization, it was observed that the highest moisture contents were found in the pulp (values around 83,29%), with the exception of the Margarida variety, that the seed had moisture (60%) higher than the pulp (36,31%) and bark (34,68%). The soluble solids content with values around 9°Brix shows the optimal maturation stage for harvesting. The highest lipid content (11,43%) was found in the pulp of the Breda variety. The identification and quantification of bioactive compounds using modern techniques such as high-performance liquid chromatography coupled with mass spectrometry (LC-MS) showed compounds such as chlorogenic acid (2,61 mg/mL), catechin (1,92 mg/mL) in the Geada variety and succinic acid (2,31 mg/mL) in Margarida at reasonable concentrations arousing interest in the properties of these compounds.